Analysis of waste management policies based on village owned enterprises (Bumkal) (empirical study on Caturharjo Village) - Rechandy Christian Adhitya (BIO Web of Conferences)
The problem of waste is a serious thing to be handled in Yogyakarta and overcoming waste through its source is an interesting thing to research. The purpose of this study is to find out the waste management based on Village-Owned Enterprises (BUMKAL) in Caturharjo Village which has succeeded in building waste management through BUMKAL Catur Sejahtera. This research uses a qualitative approach by conducting direct interviews with stakeholders and the community in waste management in Caturharjo Village. The results of this study revealed that Caturharjo Village through Perkal Number 2 of 2022 concerning waste management using (1). Waste collection is not harmful, (2). Waste management and disposal are not hazardous, (3). Community- and community-based organic compost production, (4). Combined provider of facility supports services. In addition, the findings saw that Caturharjo Village also carried out pentahelix collaboration to solve waste in Caturharjo Village.